Association Between Consecutive Days Worked by Intensivists and Outcomes for Critically Ill Patients. Issue 4 (April 2020) - Gershengorn, Hayley B.; Pilcher, David V.; Litton, Edward; Anstey, Matthew; Garland, Allan; Wunsch, Hannah
Abstract : Objective: To evaluate the association between consecutive days worked by intensivists and ICU patient outcomes. Design: Retrospective cohort study linked with survey data. Setting: Australia and New Zealand ICUs. Patients: Adults (16+ yr old) admitted to ICU in the Australia New Zealand Intensive Care Society Centre for Outcome and Resource Evaluation Registries (July 1, 2016, to June 30, 2018). Interventions: None. Measurements and Main Results: We linked data on staffing schedules for each unit from the Critical Care Resources Registry 2016–2017 annual survey with patient-level data from the Adult Patient Database. The a priori chosen primary outcome was ICU length of stay. Secondary outcomes included hospital length of stay, ICU readmissions, and mortality (ICU and hospital). We used multilevel multivariable regression modeling to assess the association between days of consecutive intensivist service and patient outcomes; the predicted probability of death was included as a covariate and individual ICU as a random effect. The cohort included 225, 034 patients in 109 ICUs. Intensivists were scheduled for seven or more consecutive days in 43 (39.4%) ICUs; 27 (24.7%) scheduled intensivists for 5 days, 22 (20.1%) for 4 days, seven (6.4%) for 3 days, four (3.7%) for 2 days, and six (5.5%) for less than or equal to 1 day. Compared with care by intensivists working 7+ consecutive days (adjusted ICU length of stay = 2.85 d), care by an intensivist working 3 or fewer consecutive days was associated with shorter ICU length of stay (3 consecutive days: 0.46 d fewer, p = 0.010; 2 consecutive days: 0.77 d fewer, p < 0.001; ⩽ 1 consecutive days: 0.68 d fewer, p < 0.001). Shorter schedules of consecutive intensivist days worked were also associated with trends toward shorter hospital length of stay without increases in ICU readmissions or hospital mortality. Conclusions: Care by intensivists working fewer consecutive days is associated with reduced ICU length of stay without negatively impacting mortality. Abstract : Supplemental Digital Content is available in the text.